HANDS-ON ACTIVITY ABOUT WIRELESS ELECTRICITY TO PHYSICS UNDERGRADUATE STUDENTS - Pinto, Pedro Haerter; Tel, Guilherme Tavares; Oliveria, Milena Chierrito; Danhoni, Marcos (International Journal of Research -GRANTHAALAYAH, 2020)
This paper presents a physical experiment, involving wireless electricity, in a workshop for students entering in an undergraduate course in Physics as a way to stimulate interaction between students, seeking to achieve meaningful learning through an example that can be generalized during the course.